PENGARUH KONSENTRASI ZAT PENGATUR TUMBUH (ZPT) ROOT UP TERHADAP PERTUMBUHAN STEK BATANG JARAK PAGAR (Jatropha curcas) - Prama Yudha Setia Darma; Ina Darliana (Fakultas Kehutanan Universitas Winaya Mukti, 2022)
Jatropha curcas (Jatropha curcas) is a woody shrub that is widely found in tropical areas. This plant is known to be very drought tolerant and easily propagated by cuttings. The oil that comes from the fence is used as fuel (biodiesel). The object of research was to find out the influence of Root Up Growth Regulating Substance (ZPT) concentration on the growth of Jatropha stem cuttings. The method of research used is an experimental method using a Group Randomized Design (RAK) with the treatment of Root Up Growth Regulators (ZPT) concentrations of 0 mg, 20 mg, 25 mg, 30 mg, and 40 mg repeated 10 times. The observed variables are, number of roots, average length of roots, number of shoots, and average length of shoots. The results obtained from giving ZPT Root up with concentrations of 0 mg, 20 mg, 25 mg, 30 mg, and 40 mg had no significant effect on the growth of the number of roots, average root length, number of shoots, and average shoot length. No significant influence of concentration was found, but seen from DMRT there was a tendency for the P2 treatment with a concentration of 25 mg to show the best average shoot length.